Rehabilitation of Patients with Rheumatic Diseases - An Update - Uddin, Md Taslim; Moyeenuzzaman, Md; Hasan, Suzon Al (TAJ: Journal of Teachers Association, 2009)
Rehabilitation stands to make a person fit again. Rheumatic diseases are a heterogeneous group of disorders that involve joint structures (synovium, cartilage and bone) and their surrounding soft tissues (skin, muscles, tendons and ligaments). This chronic process results in soft tissue and synovial swelling, erosion of cartilage and bone, rupture of tendons, ligaments and joint capsule, reduction in joint space, muscle wasting and osteoporosis. Disease progression can create marked joint instability, muscular weakness and a reduction of general fitness. Rehabilitation of rheumatic patients includes multidisciplinary approach with pharmacotherapy, thermotherapy and cryotherapy, optimal rest, use of orthoses and functional aids, exercises, surgery and patient education. The present article will highlight biomechanical factors in the causation of disability and an approach to rehabilitate this group of patients. doi: 10.3329/taj.v16i2.3890 TAJ December 2003; Vol.16(2): 82-88